2014
DOI: 10.1155/2014/698538
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Displacement of a Foreign Body into the Periapical Tissues

Abstract: The presence of a foreign body in the periapical tissues can cause endodontic failure by triggering an inflammatory response and a subsequent foreign body reaction. This inflammatory response, which can occur to varying degrees, appears radiographically as a radiolucency that can remain asymptomatic for many years. A foreign object can reach the apical region by accident or iatrogenic procedures during dental procedures. The aim of the present case report is to describe the endodontic surgical treatment of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…The results of this study confirmed that the 30-50 years age group was most commonly submitted to treatment (42%) as reported by previous studies (28,29) . Completely formed teeth can suffer alteration in the terminal portion of the root by pathological or iatrogenic factors and develop open apices.…”
Section: Resultssupporting
confidence: 91%
“…The results of this study confirmed that the 30-50 years age group was most commonly submitted to treatment (42%) as reported by previous studies (28,29) . Completely formed teeth can suffer alteration in the terminal portion of the root by pathological or iatrogenic factors and develop open apices.…”
Section: Resultssupporting
confidence: 91%
“…The classical CALDWELL-LUC approach is performed if for size or anatomical considerations the endoscopic retrieval is difficult or impossible. [2][3][4][5][6]…”
Section: Discussionmentioning
confidence: 99%
“…Open apices include a wide variety of cellular changes and radicular morphologies throughout all phases of root development ( 19 ). When a tooth remains more immature, it becomes more difficult to mechanically clean the pulpal space, the risk of foreign body extrusion inside the periapical tissues increases due to the lack of apical constriction, and the presence of apical divergent anatomy ( 20 , 21 ). Although several classification systems for radicular formations have been proposed ( 13 - 15 ), the Cvek ( 11 ) classification criteria were used in this study due to the didactic radiographic characteristics of this system, which allows for better clinical application than that used in the other classification schemes.…”
Section: Discussionmentioning
confidence: 99%